2019
DOI: 10.1039/c9sc00290a
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembly of two robust 3D supramolecular organic frameworks from a geometrically non-planar molecule for high gas selectivity performance

Abstract: Two 3D SOFs were synthesized based on a ‘direction-oriented’ strategy. The unique and permanent porosity structures exhibit remarkable ability to separate CO2 from N2 and light hydrocarbons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 64 publications
0
21
0
Order By: Relevance
“…Slow evaporation of an ethyl ether solution into a THF solution of TMBTI in two weeks afforded the colorless stick‐like crystals. During our exploration of the activated ZJU‐HOF‐1, the structure of the as‐synthesized HOF (JLU‐SOF3) was independently reported for different properties [13c] . Single crystal X‐ray diffraction analysis revealed that JLU‐SOF3 crystallizes in a hexagonal P true6 2 c space group with a hydrogen‐bonded 3D network (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Slow evaporation of an ethyl ether solution into a THF solution of TMBTI in two weeks afforded the colorless stick‐like crystals. During our exploration of the activated ZJU‐HOF‐1, the structure of the as‐synthesized HOF (JLU‐SOF3) was independently reported for different properties [13c] . Single crystal X‐ray diffraction analysis revealed that JLU‐SOF3 crystallizes in a hexagonal P true6 2 c space group with a hydrogen‐bonded 3D network (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, new supramolecular porous materials named hydrogen-bonded organic frameworks (HOFs) or supramolecular organic frameworks (SOFs) have been developed [25][26][27][28][29][30][31][32][33][34][35][36]. Usually, a HOF is built from multitopic tectons that interact with their neighbors by directional hydrogen bonds, disfavoring close packing, and thus generating significant pore volumes within the crystal [25][26][27][28]. These heterogeneous, crys-talline, supramolecular frameworks may be neutral, for example, those built by mutual interactions of multitopic carboxylic acids [25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Usually, a HOF is built from multitopic tectons that interact with their neighbors by directional hydrogen bonds, disfavoring close packing, and thus generating significant pore volumes within the crystal [25][26][27][28]. These heterogeneous, crys-talline, supramolecular frameworks may be neutral, for example, those built by mutual interactions of multitopic carboxylic acids [25][26][27][28][29]. Alternatively, they can be constructed from components possessing oppositely charged multitopic tectons, in which case the framework becomes a charge-assisted hydrogenbonded framework (CAHOF), as was the case when multitopic guanidinium or amidinium cations were combined with polycarboxylates, polysulfonates, or polyphosphonates [30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We and others have contributed to the design of 3D HOFs using geometrically well-defined trigonal prismatic carboxyl building blocks. Our molecular design is based on the use of triptycene as the backbone in order to take advantage of (1) its rigid bicyclic structure that prevents close packing in the solid state for the introduction of porosity and (2) the ease of its peripheral functionalization that allows the installation of six aryl-carboxyl groups, affording a highly modulable trigonal prismatic scaffold.…”
Section: D Hofs With Trigonal Prismatic Building Blocksmentioning
confidence: 99%